A case of thymoma presenting as pyrexia of unknown origin - Vikas Marwah; Robin Choudhary; V Shrinath; Gourang Paliwal (Indian Journal of Pathology and Microbiology)
Pyrexia of unknown origin can be caused due to numerous infective and noninfective causes. It poses a diagnostic dilemma to the clinicians and requires a myriad of investigations for the confirmation of diagnosis. Thymomas are rare mediastinal tumors that present as anterior mediastinal mass; however, thymomas presenting as pyrexia of unknown origin has rarely been reported in the literature. We report an interesting case of a middle-aged male who presented as pyrexia of unknown origin due to thymoma.